PENGEMBANGAN BAHAN AJAR GEOMETRI BERBASIS ETNOMATEMATIKA MELAYU KAMPAR UNTUK MENINGKATKAN PENALARAN MATEMATIS SISWA SEKOLAH DASA - Fatmawilda; Zetra Hainul Putra, Neni Hermita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low mathematical reasoning ability of students and the lack of students' knowledge about local wisdom around them. In addition, teachers also find it difficult to create teaching materials that can increase student motivation and mathematical reasoning abilities. This study aims to produce valid, practical, and effective teaching materials to improve elementary school students' mathematical reasoning abilities. This study uses research and development. The development model used in this study is the ADDIE model or Analyze, Design, Development, Implementation, Evaluation. The subjects of the study were fourth grade students of SDN 035 Taraibangun. The data collection techniques used were interviews, observations, and tests. The data analysis technique used qualitative data analysis and quantitative data analysis. The results of the study indicate that the geometry teaching materials based on the ethnomatics of Kampar Malay culture have met the criteria of very valid, very practical, and effective in improving students' mathematical reasoning abilities in elementary schools.